A New Strategy to Improve Proactive Route Updates in Mobile Ad Hoc Networks. Issue 5 (12th December 2005) - Abolhasan, Mehran; Wysocki, Tadeusz; Lipman, Justin
Abstract : This paper presents two new route update strategies for performing proactive route discovery in mobile ad hoc networks (MANETs). The first strategy is referred to as minimum displacement update routing (MDUR). In this strategy, the rate at which route updates are sent into the network is controlled by how often a node changes its location by a required distance. The second strategy is called minimum topology change update (MTCU). In this strategy, the route updating rate is proportional to the level of topology change each node experiences. We implemented MDUR and MTCU on top of the fisheye state routing (FSR) protocol and investigated their performance by simulation. The simulations were performed in a number of different scenarios, with varied network mobility, density, traffic, and boundary. Our results indicate that both MDUR and MTCU produce significantly lower levels of control overhead than FSR and achieve higher levels of throughput as the density and the level of traffic in the network are increased.